2014
DOI: 10.1007/s10661-014-3870-y
|View full text |Cite
|
Sign up to set email alerts
|

Community metabolism in a deep (stratified) tropical reservoir during a period of high water-level fluctuations

Abstract: As long as lakes and reservoirs are an important component of the global carbon cycle, monitoring of their metabolism is required, especially in the tropics. In particular, the response of deep reservoirs to water-level fluctuations (WLF) is an understudied field. Here, we study community metabolism through oxygen dynamics in a deep monomictic reservoir where high WLF (~10 m) have recently occurred. Simultaneous monitoring of environmental variables and zooplankton dynamics was used to assess the effects of WL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(57 citation statements)
references
References 52 publications
8
46
0
3
Order By: Relevance
“…Cyanobacteria bloomed at the surface water in August, and had an obvious vertical gradient in the water, as reported in other aquatic ecosystems [53]. Moreover, it is suggested that the blooms of Cyanobacteria are favored by the lack of mixing in the water body by Valdespino-Castillo et al [46]. Additionally, both Chlorobi and Chloroflexi were detected, with a higher abundance in the hypolimnion than in the epilimnion, and were dynamically affected by stratification.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Cyanobacteria bloomed at the surface water in August, and had an obvious vertical gradient in the water, as reported in other aquatic ecosystems [53]. Moreover, it is suggested that the blooms of Cyanobacteria are favored by the lack of mixing in the water body by Valdespino-Castillo et al [46]. Additionally, both Chlorobi and Chloroflexi were detected, with a higher abundance in the hypolimnion than in the epilimnion, and were dynamically affected by stratification.…”
Section: Discussionsupporting
confidence: 53%
“…Habitat heterogeneity was considered to play an important role in the determination of microbial community structure [20,25,45]. It is suggested that thermal conditions were the main factor affecting community metabolism and structure by altering hydrodynamic processes, water movement, and mixing events in the water bodies during the annual stratified period [46]. Thus, in this study, it appeared that the dramatic shifts in DO and water temperature among different layers were the main direction indices for the differences in the bacterial communities.…”
Section: Discussionmentioning
confidence: 68%
“…Reservoir management for fish production may also be disproportionately important in tropical systems. Since most freshwater fish production comes from the tropics, management of these systems often includes introduction of new species adapted to the reservoir environment, stocking, and management of fishing effort (van Zwieten et al 2011). Our proposed conceptual model is thus likely to differ for tropical ecosystems; however, more research is needed to formulate specific hypotheses about differential fates of E and m in these systems (Fig.…”
Section: Latitude Matters: Addressing the Temperate Lake Biasmentioning
confidence: 99%
“…Water level fluctuations, caused by monsoonal climate and artificial drawdown can alter the hydrological conditions and influence light and nutrient availability, influencing phytoplankton succession (Tian et al 2015). The decrease in water level can indirectly affect the physical-chemical and biological characteristics of freshwater bodies, mainly through mixing enhancement (Valdespino-Castillo et al 2014). Extreme decreases in reservoir water level can affect the thermal structure of the water column (Zohary and Ostrovsky 2011).…”
Section: Model Performance For Water Balance and Water Temperaturementioning
confidence: 99%
“…Many reservoirs are characterized by frequent fluctuations in their water level (Wantzen et al, 2008). These fluctuations affect phytoplankton biomass and species composition through their effect on mixing processes, biogeochemical processes, oxygen dynamics, and underwater light climate (Naselli-Flores and Barone, 1997;Valdespino-Castillo et al, 2014). Their amplitude and frequency are modified by climate change because of changes in the occurrence of drought and heavy rainfall episodes (Callieri et al, 2014).…”
Section: Introductionmentioning
confidence: 99%